Escorts Afrolatinos en la Era Digital, O el Arte de Los Masajistas - Reyes-Gil, S (College of Humanities, Modern Languages 345, 2017)
This article explores images of Afro-Latin men that appeared in gay dating phone applications during 2015. Photographs and profiles of escorts traveling to Chile are analyzed to discuss, among other themes, the ambivalent structure of African cultural representations in Chile, considering the change from printed to digital media, their respective contents, modes of production, and circulation. The article studies the forms of interaction that these devices and platforms encourage, the constructions of the Afro-Latin as stereotype, as well as other methods that escorts use to promote themselves. These profiles reveal how the prejudices of the African man or mulatto are reproduced. At the same time, the article argues that in these virtual profiles we can find autonomous strategies of self-representation. © 2017 by the University of Texas Press.